Transparent, Flexible Silicon Nanostructured Wire Networks with Seamless Junctions for High-Performance Photodetector Applications - Boland, John; Mc Closkey, David (My University, 2018)
Optically transparent photodetectors are crucial in next-generation optoelectronic applications including smart windows and transparent image sensors. Designing photodetectors with high transparency, photoresponsivity, and robust mechanical flexibility remains a significant challenge, as is managing the inevitable trade-off between high transparency and strong photoresponse. Here we report a scalable method to produce flexible crystalline Si nanostructured wire (NW) networks fabricated from silicon-on-insulator (SOI) with seamless junctions and highly responsive porous Si segments that combine to deliver exceptional performance. These networks show high transparency (∼92% at 550 nm), broadband photodetection (350 to 950 nm) with excellent responsivity (25 A/W), optical response time (0.58 ms), and mechanical flexibility (1000 cycles). Temperature-dependent photocurrent measurements indicate the presence of localized electronic states in the porous Si segments, which play a crucial role in light harvesting and photocarrier generation. The scalable low-cost approach based on SOI has the potential to deliver new classes of flexible optoelectronic devices, including next-generation photodetectors and solar cells.
PUBLISHED
cited by 1
Keywords: Silicon nanostructured wire network; Photodetector; Porous silicon; Nanoscience & Materials; AMORPHOUS-SILICON; DEVICE; DOPED SILICON; FLEXIBLE; Flexible conducting device; Flexible device; JUNCTIONS; NANOCONTACTS; NANOSCALE; NANOSTRUCTURES; NANOWIRE FORMATION; NANOWIRES; Nanotechnology; Optoelectronics; POROUS SILICON; SILICON; SILICON DETECTORS; SILICON-ON-INSULATOR; Semiconductor optoelectronics; TRANSPARENT; Transparent conducting device; Transparent device; nanopores; nanowire network; photodetector; seamless; seamless junction; seamless nanowire junction; seamless nanowire network